Varian B.1.1.7 (SARS-CoV-2): Studi Literatur Singkat - Rosa Berlina Haridas; Mahatma Rota Kurnia; Hafizh Zahra; Gusnia Meilin Gholam (Jurnal Kesehatan Indonesia, 2021)
A new variant of the SARS-CoV-2 virus (i.e., B.1.1.7) has been found in Indonesia. The lack of information regarding this new variant may cause public concern. This literature aimed to provide knowledge regarding variant B.1.1.7, sourced from the following databases: Science Direct, PubMed, Semantic Scholar, and Google Scholar. This literature described the chronology of the discovery of variant B.1.1.7, all occurred mutations (especially in spike proteins), and the impact of these mutations on virus characteristics. This paper also explained the effectiveness of the vaccines circulating worldwide and the development efforts that had been carried out. Besides that, the latest information on surveillance efforts to improve the efficiency of virus detection and prevent the spread of the SARS-CoV-2 virus, either variant B.1.1.7 or other variants, was also reported.